2003
DOI: 10.1002/elps.200390175
|View full text |Cite
|
Sign up to set email alerts
|

Chiral resolution of some environmental pollutants by capillary electrophoresis

Abstract: The chiral resolution of the environmental pollutants by capillary electrophoresis is reviewed. Various aspects of the chiral resolution such as chiral selectors, optimization of capillary electrophoresis conditions including composition of the background electrolyte (BGE), pH of the BGE, ionic strength of the BGE, structures and types of the chiral selectors, applied voltage, temperature, structures of the chiral pollutants, use of organic modifiers and other parameters are presented. Furthermore, detection, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 58 publications
0
15
0
Order By: Relevance
“…Although chiral separations by CE have been recently reviewed in food analysis [7], drugs [4,5], peptides [8], in nonaqueous media [9,10], etc., few articles have reviewed the chiral separation of pollutants [11][12][13]. The most recent of these articles [13] reports the chiral resolution of some environmental pollutants, mainly pesticides, without compiling the published articles concerning this topic (in that paper, special emphasis was put on the influence of different parameters as type of chiral selector, pH of BGE, applied voltage, temperature, etc., on the chiral resolution).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although chiral separations by CE have been recently reviewed in food analysis [7], drugs [4,5], peptides [8], in nonaqueous media [9,10], etc., few articles have reviewed the chiral separation of pollutants [11][12][13]. The most recent of these articles [13] reports the chiral resolution of some environmental pollutants, mainly pesticides, without compiling the published articles concerning this topic (in that paper, special emphasis was put on the influence of different parameters as type of chiral selector, pH of BGE, applied voltage, temperature, etc., on the chiral resolution).…”
Section: Introductionmentioning
confidence: 99%
“…The most recent of these articles [13] reports the chiral resolution of some environmental pollutants, mainly pesticides, without compiling the published articles concerning this topic (in that paper, special emphasis was put on the influence of different parameters as type of chiral selector, pH of BGE, applied voltage, temperature, etc., on the chiral resolution). In view of the importance of the separation of chiral contaminants, the goal of this work is, therefore, to review the chiral separation of pollutants and metabolites by capillary electromigration methods, with special emphasis on those articles published in the last 10 years.…”
Section: Introductionmentioning
confidence: 99%
“…The agrochemical industry and government regulators are beginning to take enantioselectivity into account and several papers have been reported showing differences in the toxicities and the biodegradation behaviour between enantiomers [4 -6]. To obtain information on the toxicity and biotransformation of the chiral pollutants it is necessary to develop suitable methods for the chiral resolution of pollutants [7]. In bibliography, some references about the enantiomeric separation of some pesticides have been reported [7 -10].…”
Section: Introductionmentioning
confidence: 99%
“…The formation of CDbased guest-host complexes is a simple model for studying molecular recognition processes and has been employed in many applications (see [1,5,6] and the references cited therein) in, for example, pharmaceutical, cosmetic and food industries. In separation methods, CDs are frequently used as buffer modifiers to increase selectivity, and are especially used as chiral selectors to optimize the separation of enantiomers in CZE (see [7][8][9][10][11] and the references cited therein). Theoretically, a simple guest-host complex model based on binding equilibria has been shown to excellently explain the effect of changing the concentration of selectors on the resolution of enantiomer separation [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The apparent binding constants of these guest analytes were evaluated by a simple nonlinear regression model, which showed that b-CD is the better complex-forming host CDs with NS anions. Determining the binding constants between the charged guest compounds and the neutral CDs (native or derivatized) by CE method has been studied extensively (see [7][8][9][10][11]25] and the references cited therein). The binding constants of ionic analytes are relatively low because the analytes are hydrophilic.…”
Section: Introductionmentioning
confidence: 99%